Penerapan Analisa SWOT dan Triangulasi Teknik dalam Pemberdayaan Perempuan dan Peningkatan Ekonomi Keluarga Pengrajin Kekeba Mini - Resti Yulistria; Vina Islami; Susilawati Susilawati (Swabumi, 2020)
Empowerment of women has the aim of developing all the potential that women have, this empowerment is carried out through activities that can improve the welfare of women, especially helping improve the family economy. Methods of data collection with technical triangulation, to test the credibility of the data is done by checking the data to the same source with different techniques, in other words when the researcher has obtained data from the interview method, it is necessary to check again with other methods such as observation and documentation. So that it can be ascertained that the data is considered valid. Furthermore, a SWOT analysis is carried out, this analysis is used to formulate qualitatively and holistically both the internal and external environment of the entity being observed. The results of the research, First, the deepening of several industrial centers in the village of Sukajaya, Sukabumi District has different dynamics and characteristics. such as identity, age and education and the length of time workers have worked in centers in the location of this study, and Fourth, in order to realize the empowerment of women workers, integrated support is needed, both local agencies and community institutions (civil society), the private sector and educational institutions.  Keywords: Empowerment, women